2022
DOI: 10.1111/jomf.12836
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal influences among marital relationship, Parent–adolescent relationship, and youth depressive symptoms

Abstract: Drawing on the family systems framework, this study investigated the reciprocal prospective associations between marital relationship quality, parent-adolescent closeness and conflict, and adolescent depressive symptoms among families in Taiwan. Background: The family systems theory posits reciprocity between family subsystems. However, the direction of influences between marital relationship quality, parentadolescent relationship quality and adolescent well-being may be more unidirectional in Chinese societie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 110 publications
3
21
0
Order By: Relevance
“…Several medium-confidence CpGs from the exploratory EWAS discovery identified in PBMCs are associated with immune function or reside within or near immune-related genes. Specifically, TNF , a key immune gene encoding tumor necrosis factor alpha (TNF-α) [87], has been linked to early-life adversity, such as childhood maltreatment [2,7,8]. Furthermore, differential DNAm of TNF was shown to be associated with early protective parenting and later proinflammatory responses [10,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several medium-confidence CpGs from the exploratory EWAS discovery identified in PBMCs are associated with immune function or reside within or near immune-related genes. Specifically, TNF , a key immune gene encoding tumor necrosis factor alpha (TNF-α) [87], has been linked to early-life adversity, such as childhood maltreatment [2,7,8]. Furthermore, differential DNAm of TNF was shown to be associated with early protective parenting and later proinflammatory responses [10,24].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental programming models, such as the Developmental Origins of Health and Disease (DOHaD) [95] and the Predictive-Adaptive Response model [96], posited that children may develop phenotypes considered adaptive to stimuli in their early environment but contribute to later adverse health outcomes. Specifically, exposure to cumulative FA in early life may induce a chronic proinflammatory state in children, reflected by changes in the proportion of immune cells in blood, increased cytokine levels, and DNAm of key immune-related genes [2,7,97]. Indeed, several studies showed that early-life stress exposure was associated with elevated levels of both CRP and IL-6 in children [98,99].…”
Section: Famentioning
confidence: 99%
“…It may be a result of cultural differences. Taiwanese families tend to follow a hierarchical structure in which parents and adolescents are less egalitarian compared to Western families (Chiang & Bai, 2022; Chuang et al., 2021). To maintain parental authority, it is possible that parents may not express conflict with adolescent children, which, in turn, reduces adolescents' exposure to interparental conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Western families, families in Chinese culture, such as Taiwan, tend to emphasize interdependence, filial piety, and relationship harmony (Chiang & Bai, 2022; Fang et al., 2022). Family relationship quality has been consistently linked to child and adolescent emotional development and well‐being in Chinese societies (Jhang, 2017; Xing et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Last, we recruited adolescent participants in Taiwan, which may limit the generalization of the results to other cultures and regions. For instance, research has shown that compared to independent and egalitarian values in Western families, Taiwanese families tend to emphasize the interdependence between family members (Chiang & Bai, 2022a). This may exacerbate the close links between family relationships and adolescent psychological well-being across adolescence.…”
Section: Limitationsmentioning
confidence: 99%